Staphylococcus aureus Nasal Colonization Differs among Pig Lineages and Is Associated with the Presence of Other Staphylococcal Species - Verstappen, Koen M.; Willems, Eveline; Fluit, Ad C.; Duim, Birgitta; Martens, Marc; Wagenaar, Jaap A. (Frontiers in Veterinary Science, 2017)
Staphylococcus aureus is a common colonizer in pigs, with methicillin-resistant S. aureus (MRSA) in particular being a potential health risk to humans. To reduce the exposure to humans, the colonization in pigs should be reduced. The aim of this study was to quantitatively compare the susceptibility of pig lineages for S. aureus colonization, and if the absence of S. aureus could be associated with the presence or absence of other staphylococcal species. Nasal samples (n = 129) were obtained from seven different pig lineages in the Netherlands, France, and Germany. S. aureus and other staphylococci were enumerated from these samples by real-time (RT)-PCR and culture. Associations were explored between the presence of S. aureus and other staphylococci. S. aureus was detected by RT-PCR on all farms and in samples from pigs of all lineages. Twenty-five percent of the pigs from lineage F (from two farms) were colonized with S. aureus, while in all other lineages it was more than 50% (p < 0.01). Moreover, in S. aureus-positive samples from pigs of lineage F smaller amounts of S. aureus were found than in other lineages. Staphylococcus sciuri, Staphylococcus cohnii, and Staphylococcus saprophyticus were usually not found in combination with S. aureus in these samples. In conclusion: (i) pigs from different genetic lineages have different susceptibilities for colonization with S. aureus. These pigs might contain a genetic factor influencing nasal colonization. (ii) Colonization of S. aureus is also associated with the absence of S. sciuri, S. cohnii, or S. saprophyticus. (iii) The farm environment seems to influence the presence of S. aureus in pigs.